Human resources development: issues challenges and practices - Kudus, Norliah (Penerbit UTeM Press, 2024)
Human Resources Development: Issues, Challenges and Practices is a comprehensive guide on the complex world of managing human resources in modern organizations. It covers topics like training, talent management, performance appraisal, employee engagement, diversity management, and emerging trends like AI and VR integration. The book equips students, scholars, and practitioners with knowledge and tools to navigate the complexities of HRD effectively, fostering a skilled, engaged, and resilient workforce.